Development of methods for estimating the environmental risk of degradation of the surface water state - Rybalova, O.; Artemiev, Sergey; Sarapina, M.; Tsymbal, Bohdan; Bakhareva, A.; Shestopalov, O.; Filenko, O. (PC Technology center, 2018)
We presented three new methods for assessment of the environmental risk of deterioration of a surface water state. We defined the ecological risk of deterioration of surface water at the state level as an addition of the integrated parameter of the state of surface waters and the integral index of anthropogenic loading. We used the official information of the National Report on the state of the environment of Ukraine to calculate the mentioned indicators. We developed classifications of anthropogenic loading on aquatic ecosystems and ecological risk of deterioration of water ecosystems. The assessment of the ecological risk of deterioration of surface water state in Ukraine showed that there are watercourses of the Siversky Donets river basin in the most dangerous state. A base of the methodology for assessment of the risk of water ecosystem well-being disruption is the determination of all parameters of the state of quality of surface waters that exceed the ecological standards using the probit-regression model. The process of determining ecological risk for watercourses of the Siversky Donets river basin in Kharkiv region showed a high level of danger to the well-being of the water ecosystem of the Udi river. We obtained the forecast of climatic changes by parameters of temperature and volumes of precipitation in Kharkiv region. We investigated the dynamics of wastewater discharge to the Udi river for the period from 1992 to 2016. The study on an influence of natural and anthropogenic factors on the ecological state of the Udi river revealed that the impact of wastewater discharge with a correlation coefficient of 0.747 is a significant factor. The application of a new methodology for assessment of the risk of degradation processes made it possible to determine a list of small rivers in Kharkiv region, which require implementation of measures based on the analysis of water use efficiency, taking into consideration landscape and ecological features of a catchment area. We proposed an algorithm for the improvement of water protection strategy based on determining the ecological risk of deterioration of the condition of surface water at the state, regional and local levels. The improvement of water preservation strategy aims at introduction of an integrated interactive surface water quality management.

Проведено аналіз основних принципів і методів утилізації токсичних промислових відходів, що містять важкі кольорові метали. Наведено результати експериментів по обробці донних опадів хвостосховищ в сірчанокислому середовищі. Запропоновано схеми їх переробки, що дозволяє досягти максимальних показників вилучення основних цінних компонентів. Запропоновані технологічні рішення дозволять підвищити ефективність переробки зазначених видів техногенних відходів.
Розробка методів оцінки екологічного ризику погіршення стану поверхневих вод
Keywords: water protection strategy; ecological risk; climate change; rational use of water; river basin; техногенні відходи; важкі кольорові метали; очищення стічних вод; відходи гальваноцехів